Applications of graphene-based composites in the anode of lithium-ion batteries - Liu, Zhiming; Tian, Yu; Wang, Peng; Zhang, Guoxin (Frontiers in Nanotechnology, 2022)
In lithium-ion batteries, the traditional graphite anode material has failed to meet the demand for its development as a power battery due to the disadvantages of low theoretical capacity, slow lithium ion deintercalation rate and low energy density. In recent years, graphene has received much attention for its unique physical and chemical properties as a potential anode material. This review outlines the application of graphene materials in the anode of lithium-ion batteries and looks into its future development.